Sequence variation analysis and characterization of defence and stress-related genes in Coconut cadang-cadang viroid inoculated oil palm seedlings - Minhad, Nurulatika (2018)
Coconut cadang-cadang viroid (CCCVd) is associated with an orange spotting (OS) disorder, which is an emerging problem recently reported affecting oil palms in Malaysia. CCCVd variants were shown to contain low concentrations of several sequence variants of CCCVd in both OS and asymptomatic palms. Knowledge of interaction between CCCVd-infected oil palm is lacking and no study on defence and stress genes upon infection of CCCVd to date. Plant response has become an important approach to understand the host-pathogen interaction. The study was undertaken to study sequence variation of CCCVd oil palm variants from inoculated oil palm seedlings using RT-PCR, cloning and sequencing. Subsequently, detection and characterization of defence and stress genes in CCCVd inoculated oil palm seedlings were investigated. A total of 30 oil palm seedlings comprising ten healthy seedlings, ten seedlings inoculated with plasmid of CCCVd246OP and CCCVd293OP were used. Total nucleic acid was extracted using modified NETME extraction method. The presence of CCCVd variants were detected by RT-PCR using CCCVd specific primers, cloning and sequencing. For genes study, ten seedlings inoculated with CCCVd293OP and ten seedlings as control were used to express total of 11 oil palm genes consisting of 4 stress, 4 defence and 3 reference genes. Optimization using gradient PCR and validation of genes were carried out for real-time PCR reaction. The detection of genes were preceded with quantitative real-time PCR using SYBR Green-I. For sequence variation study, RT-PCR analysis showed that all seedlings inoculated with plasmid CCCVd246OP and CCCVd293OP were detected and generated amplicons at approximately 300 nt on 2% agarose gel electrophoresis. There was no OS symptoms observed for both CCCVd variants. Results of sequencing showed that none of the clones of CCCVd246OP were positive with CCCVd, whereas seedlings inoculated with CCCVd293OP had 99-100% sequence similarity to CCCVd variant 293 nt (DQ097184). Five clones had two to three base substitutions in their sequence compared with the consensus sequence of CCCVd293OP which indicate that there were minor sequence variation. However, there are no quasispecies occurs in this study. For genes study, stress and defence genes in CCCVd-inoculated oil palm seedlings were successfully detected and characterized using conventional PCR and real-time PCR. Real-time PCR was found to be more sensitive than conventional PCR. The validation of genes through DNA sequencing was successful as the sequencing results showed 86- 100% sequence similarity to respective genes. The study showed that all the genes involved were significantly different with the control seedlings. Stress and defence genes were significantly different with the time of post-inoculation. In conclusion, there are minor sequence variation present in oil palm seedlings inoculated with CCCVd293OP and no quasispecies observed. Defence and stress-related genes were successfully detected and characterized through real-time PCR and conventional PCR in oil palm seedlings inoculated with CCCVd293OP plasmid.